Pollen holographic images and light-induced fluorescence measurements at the species level - Sophie Erb; Alexis Berne; Bernard Clot; Maria Lbadaoui-Darvas; Gian-Duri Lieberherr; Marie-Pierre Meurville; Fiona Tummon; Benoît Crouzy (Scientific Data)
Abstract The data collection presented here consists of holographic images and light-induced fluorescence measurements of pollen grains performed with the SwisensPoleno Jupiter, an instrument for real-time bioaerosol monitoring. This pollen collection, sampled directly from plants in their natural environment, is meant to provide reference datasets of airborne, mostly allergenic, pollen species found in central Europe. It has the advantage of including fluorescence measurements in addition to holographic images, giving an insight of both particle composition and morphology. Large reference datasets are necessary to develop automatic pollen monitoring tools but gathering fresh samples is complex, seasonally dependent and time consuming. Data sharing is the key to reduce data generation costs and improve identification of local and long-range transport pollen. These data are meant to be used as the basis for training new pollen identification algorithms that will make use of fluorescence measurements. Their potential reuse can also be to study pollen morphological and compositional variability at the species level.